1995
DOI: 10.1038/nm0795-674
|View full text |Cite
|
Sign up to set email alerts
|

Failure of T-cell homeostasis preceding AIDS in HIV-1 infection

Abstract: We and others have postulated that a constant number of T lymphocytes is normally maintained without regard to CD4+ or CD8+ phenotype ('blind' T-cell homeostasis). Here we confirm essentially constant T-cell levels (despite marked decline in CD4+ T cells and increase in CD8+ T cells) in homosexual men with incident human immunodeficiency virus, type 1 (HIV-1), infection who remained free of acquired immunodeficiency syndrome (AIDS) for up to eight years after seroconversion. In contrast, seroconverters who dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
138
1
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(148 citation statements)
references
References 21 publications
6
138
1
3
Order By: Relevance
“…Our observation of the upward trajectories of average CD8 cell count after HIV seroconversion is consistent with previous findings from MACS [Margolick et al, 1995]. The observed positive association between tobacco smoking and CD4 cell count was previously reported by Park and colleagues [Park et al, 1992], who found that the effect of tobacco smoking on CD4 cell count was non-specific, maximal in HIV-uninfected men, and lost three years after seroconversion.…”
Section: Discussionsupporting
confidence: 92%
“…Our observation of the upward trajectories of average CD8 cell count after HIV seroconversion is consistent with previous findings from MACS [Margolick et al, 1995]. The observed positive association between tobacco smoking and CD4 cell count was previously reported by Park and colleagues [Park et al, 1992], who found that the effect of tobacco smoking on CD4 cell count was non-specific, maximal in HIV-uninfected men, and lost three years after seroconversion.…”
Section: Discussionsupporting
confidence: 92%
“…In this vein, the immune responses induced by the bicistronic gp120-⌬Tat DNA vaccine mimicked events that occur in individuals chronically infected with HIV-1, who develop subsets of HIV-1-specific CD8 ϩ T cells that express IFN-␥ but lack cytotoxic effector functions (48,49). The immune-modulating activity of the bicistronic gp120-Tat DNA vaccine resembles events that occur in chronically infected individuals who undergo a change in clinical status concomitantly with the loss of HIV-1-specific CD8 ϩ T cells (52,53). Furthermore, the gradation of potencies displayed by the Tat DNA vaccines used in our study suggests that the degree to which CD8 ϩ T cell responses are altered by Tat depends on the bioactivity of Tat present in immune inductive sites.…”
Section: Discussionmentioning
confidence: 55%
“…The most striking result is that among all of the immunologic and virologic variables assessed in this observational study, the only significant difference during the first months of life and before the onset of PE are the CD8 ϩ T-lymphocytes. Cytotoxic CD8 ϩ T-lymphocytes (CTLs) kill virusinfected cells, and their role in the control of HIV-1 infection in vitro and in vivo is well established, although only a few studies have analyzed their prognostic value in the follow-up of infected adults [32][33][34] and children. 21,35,36 The suppression of HIV-1 replication is dependent on the presence of a relatively small number of HIV-1-specific CD8 ϩ Tlymphocyte clones, and it is possible that the duration of the neurologically asymptomatic phase for any given child may depend mostly on the magnitude of specific CD8 ϩ T-lymphocyte responses.…”
Section: Discussionmentioning
confidence: 99%